Urban sprawl analysis and modeling in Asmara, Eritreia: Application of Geospatial Tools - Tewolde, Mussie Ghebretinsae (2011)
Dissertation submitted in partial fulfillment of the requirements for the Degree of Master of Science in Geospatial Technologies.